Hypoxia Modulates Platelet Purinergic Signalling Pathways - Paterson, Gordon G.; Young, Jason M.; Willson, Joseph A.; Graham, Christopher J.; Dru, Rebecca C.; Lee, Eleanor W.; Torpey, Greig S.; Walmsley, Sarah R.; Chan, Melissa V.; Warner, Timothy D.; Baillie, John Kenneth; Thompson, Alfred Arthur Roger (Thrombosis and Haemostasis, 2020)
Background Hypoxia resulting from ascent to high-altitude or pathological states at sea level is known to increase platelet reactivity. Previous work from our group has suggested that this may be adenosine diphosphate (ADP)-specific. Given the clinical importance of drugs targeting ADP pathways, research into the impact of hypoxia on platelet ADP pathways is highly important.Methods Optimul aggregometry was performed on plasma from 29 lowland residents ascending to 4,700 m, allowing systematic assessment of platelet reactivity in response to several platelet agonists. Aggregometry was also performed in response to ADP in the presence of inhibitors of the two main ADP receptors, P2Y1 and P2Y12 (MRS2500 and cangrelor, respectively). Phosphorylation of vasodilator-stimulated phosphoprotein (VASP), a key determinant of platelet aggregation, was analysed using the VASPFix assay.Results Hypobaric hypoxia significantly reduced the ability of a fixed concentration of cangrelor to inhibit ADP-induced aggregation and increased basal VASP phosphorylation. However, in the absence of P2Y receptor inhibitors, we did not find evidence of increased platelet sensitivity to any of the agonists tested and found reduced sensitivity to thrombin receptor-activating peptide-6 amide.Conclusion Our results provide evidence of increased P2Y1 receptor activity at high altitude and suggest down-regulation of the P2Y12 pathway through increased VASP phosphorylation. These changes in ADP pathway activity are of potential therapeutic significance to high-altitude sojourners and hypoxic sea level patients prescribed platelet inhibitors and warrant further investigation.
Keywords: hypoxia; platelet physiology; anti-platelet agents; ADP receptors; high altitude